2023
DOI: 10.1002/pssa.202300206
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical, and Chemical Characteristics of High‐Quality PbI2 Thin Films via Chemical Solution Deposition with Thermal Annealing

Jeisson Javier Solis-Mosquera,
Dagoberto Cabrera-German,
Hisila Santacruz-Ortega
et al.

Abstract: Lead iodide (PbI 2 ) thin films are interesting semiconductor materials arranged in quasi 2D layers, [1] that have an optical bandgap near the ultraviolet (E g = 2.4 eV) spectrum and are composed of atoms with a high atomic mass. [2,3] These characteristics of PbI 2 allow its use in diverse applications, [4][5][6][7][8] with a recent interest in large-area visible, X-ray, and γ-ray radiation detectors. [2,9] Additionally, PbI 2 thin films are excellent precursors in the chemical synthesis of lead halide perovs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 63 publications
3
6
0
Order By: Relevance
“…For the CsPbI 1.5 Br 1.5 perovskite, the Cs 3d 5/2 and I 3d 5/2 signals are energy located at 724.80 and 619.29 eV binding energy, respectively, which are in correspondence to other reports in the literature . Also, we can observe the presence of the Pb 4f 7/2 located at 138.79 eV, associated with a Pb 2+ state and a low-intensity signal related to metallic Pb . The binding energy values of the Br 3d 5/2 and Cs 4d 5/2 are found to be 68.81 and 76.05 eV, which are similar results to what various authors have reported elsewhere …”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…For the CsPbI 1.5 Br 1.5 perovskite, the Cs 3d 5/2 and I 3d 5/2 signals are energy located at 724.80 and 619.29 eV binding energy, respectively, which are in correspondence to other reports in the literature . Also, we can observe the presence of the Pb 4f 7/2 located at 138.79 eV, associated with a Pb 2+ state and a low-intensity signal related to metallic Pb . The binding energy values of the Br 3d 5/2 and Cs 4d 5/2 are found to be 68.81 and 76.05 eV, which are similar results to what various authors have reported elsewhere …”
Section: Resultssupporting
confidence: 88%
“…10 Also, we can observe the presence of the Pb 4f 7/2 located at 138.79 eV, associated with a Pb 2+ state 43 and a low-intensity signal related to metallic Pb. 38 The binding energy values of the Br 3d 5/2 and Cs 4d 5/2 are found to be 68.81 and 76.05 eV, which are similar results to what various authors have reported elsewhere. 44 By analyzing the photoelectron spectra for the (Cs 0.95 :Cu 0.01 )PbI 1.5 Br 1.3 Cl 0.1 perovskite thin film, there exists evidence supporting that Cu atoms induced a change in the local chemical environment of the perovskite, which consists in an overall chemical shift to lower binding energies of around 0.57 ± 0.08 eV for all photoelectron signals.…”
Section: Chemical State Assessmentsupporting
confidence: 89%
See 3 more Smart Citations